2017
DOI: 10.1007/s00125-016-4193-z
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sitting may increase diabetes risk in physically inactive individuals: an 11 year follow-up of the HUNT Study, Norway

Abstract: Aims/hypothesis We examined the association between sitting time and diabetes incidence, overall and by strata of leisuretime physical activity and BMI. Methods We followed 28,051 adult participants of the NordTrøndelag Health Study (the HUNT Study), a populationbased study, for diabetes incidence from 1995-1997 to 2006-2008 and estimated HRs of any diabetes by categories of self-reported total daily sitting time at baseline. Results Of 28,051 participants, 1253 (4.5%) developed diabetes during 11 years of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 14 publications
3
38
0
1
Order By: Relevance
“…The evidence on the effects of sitting on metabolic health generated in our review is supported modestly by epidemiological evidence. Recent prospective studies of total sitting time and incident type 2 diabetes, in contrast to crosssectional studies of sedentary time and breaks measured by self-report [117], found little evidence for an association [118], or associations, between sitting behaviour or time and incident type 2 diabetes, but were limited to inactive [119] or obese [120] participants only. To resolve the discordant findings of prospective versus cross-sectional epidemiological studies, which do suggest an association between sitting time and type 2 diabetes [117], future prospective studies utilising accelerometer assessed total sitting time need to be conducted.…”
Section: Discussionmentioning
confidence: 89%
“…The evidence on the effects of sitting on metabolic health generated in our review is supported modestly by epidemiological evidence. Recent prospective studies of total sitting time and incident type 2 diabetes, in contrast to crosssectional studies of sedentary time and breaks measured by self-report [117], found little evidence for an association [118], or associations, between sitting behaviour or time and incident type 2 diabetes, but were limited to inactive [119] or obese [120] participants only. To resolve the discordant findings of prospective versus cross-sectional epidemiological studies, which do suggest an association between sitting time and type 2 diabetes [117], future prospective studies utilising accelerometer assessed total sitting time need to be conducted.…”
Section: Discussionmentioning
confidence: 89%
“…Eight articles reporting more than one health outcome were treated as independent studies . Among these studies, 21 studies (six cohort and 15 cross‐sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 23 studies (13 cohort and 10 cross‐sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, and 14 studies (one cohort and 13 cross‐sectional studies) examined the association between total sedentary behaviour and hypertension . Ten studies were conducted in North America, two in South America, nine in Australia, 18 in Europe, seven in Asia, and two in other regions .…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles reporting more than one health outcome were treated as independent studies. [28][29][30][31][32][33][34][35] Among these studies, 21 studies (six cohort and 15 cross-sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 32-52 23 studies (13 cohort and 10 cross-sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, [28][29][30][31][32][33]35,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] and 14 studies (one cohort and 13 cross-sectional studies) examined the association between total sedentary behaviour and hypertension. 27 Research and Quality scale for cross-sectional studies, which indicated that the included studies were of high quality (Table S3A,B in Appendix S1).…”
Section: Characteristics and Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have extended these works by showing the associations in an Asian population. In addition, several studies have shown an association between self-reported sitting time and the presence of diabetes mellitus 8,14,27,28 . The present findings support the notion that prolonged sedentary time increases the risk of having diabetes independent of physical activity levels.…”
Section: Discussionmentioning
confidence: 99%